Changes in Body Composition as Determinants of Longitudinal Changes in Bone Mineral Measures in 8 to 26-year-old Female Twins - Young, D.; Hopper, J. L.; Macinnis, R. J.; Nowson, C. A.; Hoang, N. H.; Wark, J. D. (Osteoporosis international, 2001)
Between 1990 and 1998, we conducted a longitudinal study of 286 female twins aged 8 to 25 years at baseline (60 monozygotic (MZ) pairs, 44 dizygotic (DZ) pairs and 78 unpaired twins), measured on average 2.4 times (range 2-6) with an average of 1.8 years between measurements (range 0.7-6.7 years). Areal bone mineral density (ABMD) at the lumbar spine, total hip and femoral neck, total body bone mineral content (BMC), total body soft tissue composition (lean mass and fat mass) were measured by dual-energy X-ray absorptiometry, and height and menarchial status were also recorded. Median annual changes in height were negligible at 4 years post-menarche. During the 'linear growth' period up to 4 years post-menarche, ABMD at the lumbar spine, total hip and femoral neck increased with annual change in lean mass by 1.7 (S.E.0.1), 1.4 (0.1) and 1.0 (0.1) percent per kilogram per year, respectively (all p<0.001), independently of changes in fat mass or height. During the 'post-linear growth' period, ABMD at the total hip and femoral neck increased with annual change in fat mass by 0.3 (0.1) and 0.5 (0.1) percent per kilogram per year (all p < 0.01), independent of change in lean mass. Annual changes in total body BMC were associated with annual changes in lean mass (1.9 (0.2) percent per kilogram), in fat mass (1.3 (0.2) percent per kilogram) and in height (0.7) (0.2) percent per centimeter) during linear growth, and in fat mass (1.0 (0.1)) and lean mass (0.6 (0.1)) percent per kilogram post-linear growth (all p < 0.001). We conclude that changes in bone mineral measures are strongly associated with changes in lean mass during linear growth, while post-linear growth, changes in fat mass are the predominant, although weaker, predictor. These findings suggest that the strong cross-sectional association between bone mineral measures and lean mass is established during growth and development, and that fat mass emerges as a more powerful determinant of bone change in healthy adult females.